Co-constructing ancestry through direct-to-consumer genetic testing - Alexander Lang; Florian Winkler (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis, 2021)
Direct-to-consumer (DTC) genetic ancestry tests offered via the internet supposedly uncover the ancestry of those tested. While these tests might be seen as a means to find a biologically inscribed and fixed genealogy, this paper explores how companies and customers co-construct ancestry through genetic ancestry testing. The study draws on a review of relevant literature, qualitative interviews with experts and stakeholders, a website analysis, and an autoethnographic self-observation. It shows how DTC genetic testing companies create specific concepts of ancestry in their marketing, development of specific databases, and presentation of results, but also how users interpret and incorporate their results into their own genealogies and lives. Looking at the potential social impact of DTC ancestry testing, the paper questions its categorization as recreational activity or entertainment.